2014
DOI: 10.1590/2317-1782/20142014040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of craniomandibular and cervical pain on the activity of masticatory muscles in individuals with Temporomandibular Disorder

Abstract: Influência da dor craniomandibular e cervical na atividade dos músculos mastigatórios em indivíduos com Disfunção Temporomandibular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 22 publications
1
35
0
4
Order By: Relevance
“…Like the results in a study previously conducted, possibly, the lower severity and lower duration of craniomandibular and neck pain in the studied sample may have justified the absence of this association 36 , as well as the lack of a more detailed analysis of correlation including the different diagnoses of TMD and the different severities found. It has already been noted that the higher the severity of TMD, the higher the severity of cervical dysfunction 37 .…”
mentioning
confidence: 51%
“…Like the results in a study previously conducted, possibly, the lower severity and lower duration of craniomandibular and neck pain in the studied sample may have justified the absence of this association 36 , as well as the lack of a more detailed analysis of correlation including the different diagnoses of TMD and the different severities found. It has already been noted that the higher the severity of TMD, the higher the severity of cervical dysfunction 37 .…”
mentioning
confidence: 51%
“…From the 17 selected studies, fifteen of them used RDC/TMD protocol for TMD diagnosis and the other two studies used the Helkimo Protocol . The studies which used RDC/TMD protocol presented a sample with only masticatory muscles disorders, a sample with mixed TMD, a sample with the 3 subtypes of TMD (TMJ disorders, masticatory muscles disorders or mixed), samples with TMJ disorders and mixed TMD, and samples with only mixed TMD . Regarding two articles that used Helkimo Protocol, one of them presented a sample with minor, moderate, and severe TMD, and the other presented a sample with moderate and severe TMD.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding two articles that used Helkimo Protocol, one of them presented a sample with minor, moderate, and severe TMD, and the other presented a sample with moderate and severe TMD. Studies which used RDC/TMD were conducted in Brazil, Chile, Italy and United States, whilst studies which used Helkimo Protocol were conducted in Mexico and Spain . A summary of the studies descriptive characteristics can be found in Table and the sEMG characteristics are available in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geralmente, os pacientes com DTM apresentam maior assimetria na ativação dos músculos temporais e masseteres, com predomínio de atividade dos músculos temporais (De Felício et al, 2013;Ries et al, 2014;Mazzetto et al, 2014).…”
Section: Eletromiografia De Superfícieunclassified